1980
DOI: 10.1007/bf02534317
|View full text |Cite
|
Sign up to set email alerts
|

Cholesteryl ester hydrolase activity in human symptomatic atherosclerosis

Abstract: Acid cholesteryl ester hydrolase (CEH) activity was assayed in mononuclear cells of patients with symptomatic atherosclerosis (transient ischemic attacks, TIA) and in age-matched controls showing no evidence of atherosclerosis. The acid CEH level of TIA patients was significantly lower than that of controls (1074 +/- 128 vs 2113 +/- 255 pmol/mg P/hr, mean +/- SE). Neither mononuclear cell nor plasma cholesterol and cholesteryl ester concentrations differed significantly between atherosclerotic and control grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0
1

Year Published

1984
1984
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 20 publications
1
12
0
1
Order By: Relevance
“…In this study, we investigated the effect of the CAD-associated coding variant, rs1051338, and found that the risk allele caused an increased degradation of LAL, resulting in reduced lysosomal levels of LAL protein and reduced activity. These results are consistent with the early onset atherosclerosis seen with loss of function LIPA mutations in CE storage disease 1521 and with data from mouse models. 2226 …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In this study, we investigated the effect of the CAD-associated coding variant, rs1051338, and found that the risk allele caused an increased degradation of LAL, resulting in reduced lysosomal levels of LAL protein and reduced activity. These results are consistent with the early onset atherosclerosis seen with loss of function LIPA mutations in CE storage disease 1521 and with data from mouse models. 2226 …”
Section: Discussionsupporting
confidence: 89%
“…Both conditions are associated with extensive lysosomal CE and triglyceride accumulation in multiple tissues, 14 and CE storage disease subjects develop premature atherosclerosis. 1521 Injection of recombinant LAL in low-density lipoprotein (LDL) receptor–deficient atherosclerotic mice prevented early atheroma formation and reduced the number of late-stage lesions, 22 while injections of recombinant LAL into LAL -deficient mice reduced cholesterol and triglyceride levels in multiple tissues. 2326 …”
mentioning
confidence: 99%
“…In this process, the free cholesterol released regulates its endogenous synthesis and esterification, as well as the uptake of low-density lipoprotein [1]. The importance of LAL in the regulation of intracellular cholesterol flux is further supported by the fact that its altered function has been implicated in the development of atherosclerosis in the population at large [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the recognized importance of HLAL in the regulation of cholesterol metabolism, difficulties with experimental manipulation of the enzyme have limited progress in understanding its control and physiological role. The observations that CESD patients exhibit premature atherosclerosis and that, conversely, a large subset of coronary artery (25) and cerebrovascular disease (26) patients have low levels of HLAL activity indicate the relevance of this enzyme's function to cardiovascular risk in the general population. This risk can now be explored with newly available molecular genetic tools that can demonstrate the etiology of the enzyme's dysfunction.…”
Section: Discussionmentioning
confidence: 99%